POLÍTICAS PÚBLICAS DE DESENVOLVIMENTO TERRITORIAL E O ENFRENTAMENTO À POBREZA RURAL: avaliação do processo de implementação do Programa Territórios da Cidadania no Município de Anajatuba MA - Ericeira, Alzira do Carmo Carvalho (2015)
Public policies of territorial development and tackling rural poverty. Implementation Process Evaluation of Citizenship Territories Program in the city of Anajatuba-MA. Assess whether the conditions that facilitate or hinder the implementation of the program's actions in the years 2008 to 2013, in that municipality. The purpose of the study was guided by the understanding that the territorial configuration of the Brazilian countryside is historically marked by uneven processes that favored restricted portion of the population, jettisoning most of it as family farmers, quilombolas peoples, indigenous, rural workers employees and agrarian reform settlers. The program is part of a set of public policies that have neoliberal inspiration and guided by the World Bank dictates, have a palliative approach, compensatory and fragmented coping rural poverty. From the study, it was found that the Citizenship Territories Program is shown limited for tackling rural poverty, since the actions implemented are fragmented and discontinuous, guided, above all, in the granting of rural credit, which has been the most implemented action Anajatuba-MA, which while necessary, are not sufficient for dealing with rural poverty. Therefore, the assessment process can contribute in changing the implementation of the program, in order to enable greater efficiency and effectiveness of their actions.